Power and protest : how marginalized groups oppose the state and other institutions - Leitz, Lisa (Research in social movements, conflicts and change ;, 2021)
'Power and protest' presents chapters that analyse the dynamics of power in social movements. Examining how marginalized groups use their identities, resources, cultural traditions, violence and non-violence to assert power and exert pressure, this volume shines a light on the interaction of these groups with governments, international organizations, businesses and universities. Including chapters which draw from multidisciplinary theories and utilise quantitative and qualitative research to examine how power shapes the context and experiences of protest, the authors analyse movements in Asia, South Africa, Arab nations, the United States and Argentina to offer insights into the power utilised by average citizens, and particularly members of marginalized groups. With contributors serving up findings based on uprisings, strikes and activist activity across the globe, the first section provides theoretical insights into the power of protest campaigns against governments or corporations. Moving on to an examination of nongovernmental institutions and cultural traditions, the authors in the second section explore the role of business and education in bringing down illegitimate governments, investigates the clashes of transnational norms, government policy and the heritage industry, and examines student protests against university policies. This volume encourages readers to reconsider their assumptions about which groups can successfully wield power in social movements.